ANALISIS KEPUASAN NASABAH TERHADAP PELAYANAN JASA PERBANKAN PADA BANK RAKYAT INDONESIA (BRI) DI JAWA TIMUR - Maswar Patuh Priyadi; Suwitho Suwitho (EKUITAS (Jurnal Ekonomi dan Keuangan), 2006)
The objective of this study is to investigate the simultaneous and the partial effect of service factors consist of reliability, responsiveness, assurance and emphaty on satisfaction of BRI customer in East Java. This study  uses the sample of BRI customer lived in branch office of Kediri, Sumenep, Banyuwangi and Bojonegoro based on purposive random sampling method. Data is estimated using multiple linear regression model.The empirical result of study by partial t-test show that reliability not influence satisfaction, but another factors like responsiveness, assurance and emphaty influence satisfaction of  BRI costumer. The result by simultaneous F-test show that reliability, responsiveness, assurance and emphaty influence satisfaction of BRI customer.